A Prospective Study to Examine Responsiveness and Minimally Important Differences (MIDs) for the CLEFT-Q Scales Following Three Cleft-Specific Operations. (April 2023) - Miroshnychenko, A; Rae, C; Wong Riff, K; Forrest, CR; Goodacre, T; Swan, MC; Slator, R; Goldstein, J; Thoma, A; Harman, K; Klassen, A
Objective : The aim of this study was to examine internal responsiveness and estimate minimally important differences (MIDs) for CLEFT-Q scales. Design : In this prospective cohort study, participants completed the CLEFT-Q appearance and health-related quality of life (HRQL) scales before and six months after cleft-related surgery. Setting : Seven cleft centres in Canada, USA and UK participated. Patients/Participants : Patients were ages 8–29 years with CL/P. Interventions : Patients underwent rhinoplasty, orthognathic or cleft lip scar revision surgery. Main Outcome Measure(s) : Internal responsiveness was examined using Cohen's d effect sizes (ESs) based on the following interpretation: 0.20–0.49 small, 0.50–0.79 moderate and ≥ 0.80 large. MIDs were estimated using two distribution-based approaches. Results : Participants had a rhinoplasty (n = 31), orthognathic (n = 21) or cleft lip scar revision (n = 18) surgery. Most participants were males (56%) and aged 8–11 years (41%). Following rhinoplasty, ESs were larger for the nose (0.92, p = 0.001) and nostrils (0.94, p < 0.001) scales than for the face scale (0.51, p = 0.003). MIDs ranged between 6.2–10.4. For orthognathic surgery, larger ES was observed for the jaws scale (1.80, p < 0.001) compared with the teeth (1.16, p < 0.001), face (1.15, p = 0.001) and lips (0.94, p < 0.001) scales. MIDs ranged between 5.9–14.4. In the cleft lip scar revision sample, the largest ES was observed for the nose scale (0.76, p = 0.03), followed by lips (0.58, p = 0.009) and cleft lip scar (0.50, p = 0.043) scales. MIDs ranged between 6.4–12.3. Conclusions : CLEFT-Q detected change in key outcomes for three cleft-specific surgeries, providing evidence of its responsiveness. Estimated MIDs will aid in interpreting this PROM.